Inputs for Philippine Hosting of APEC 2015: Food Security - Roehlano M. Briones; Ivory Myka R. Galang; Danilo C. Israel (Philippine Institute for Development Studies (PIDS), 2015)
Initiatives toward the attainment of global food security have been done not just unilaterally but also regionally and globally. Among the platforms that have made great efforts in this aspect is the Asia-Pacific Economic Cooperation (APEC). In 2015, the Philippines will host the next APEC Summit. Food security shall be high on the agenda of the Summit and of various meetings. To provide advice to the Philippine Government on the possible Philippine position on food security during its hosting, this paper recommends that the Philippines should adopt agribusiness development based on sustainable food supply chains as its priority advocacy, while continuing to promote elements of food security as expressed in the APEC road map. This "branding" integrates a strong position on blue economy with the agribusiness development and road map thrusts of the Department of Trade and Industry and the Department of Agriculture.
Keywords: 330; Philippines; food security; Blue Economy; agribusiness development; sustainable food supply chains